Hubungan antara tingkat pendidikan orang tua dengan keparahan infeksi virus dengue pada anak Di RSUP Prof. Dr. R. D. Kandou Manado - Watuna, Monica C.; Mantik, Max F.J.; Rampengan, Novie H. (e-CliniC, 2016)
Abstract: The infection of dengue virus is transmitted through the vector bite of mosquito Stegomiya aegipty and Stegomiya albopictus, The most dominant in Indonesia is serotype DEN-3. There are several factors that cause the transmission of dengue virus infection, they are: agent factor, intermediary vector, host factor and environmental factor. Prevention is needed to avoid the occurrence of disease and severity of dengue virus infection. Prevention is related with host factor, that is knowledge, attitude, behavior and action taken and one of the factors that influence this is education level. The aim of this research is to find out the correlation between the education level of parents with the severity of dengue virus infection on children in Prof. Dr. R. D. Kandou Hospital Manado. The method of this research is an analytic retrospective research with cross-sectional approach, the data was obtained by collecting data of medical records as secondary data. The data was analyzed by Gamma correlation test, obtained the value of p = 0.011 stating that there is a correlation between father's education level and severity of dengue virus infection. And also obtained the value of p = 0.002 stating that there is a correlation between mother's education level and severity of dengue virus infection.Keywords: education level, dengue virus infection, children.Â Abstrak: Infeksi virus dengue ditularkan melalui gigitan vektor nyamuk Stegomiya aegipty dan Stegomiya albopictus, di Indonesia dengan serotype DEN-3 yang paling dominan. Terdapat beberapa faktor yang memegang peranan pada penularan infeksi virus dengue yaitu faktor agent, vektor perantara, faktor host dan faktor lingkungan. Pencegahan diperlukan untuk mencegah terjadinya penyakit dan keparahan infeksi virus dengue. Pencegahan berkaitan dengan faktor host yaitu pengetahuan, sikap, perilaku serta tindakan yang dilakukan dan salah satu faktor yang memengaruhi hal tersebut yaitu tingkat pendidikan. Tujuan penelitian ini untuk mengetahui hubungan antara tingkat pendidikan orang tua dengan keparahan infeksi virus dengue pada anak di RSUP Prof. Dr. R. D. Kandou Manado. Metode penelitian ini merupakan penelitian analitik retrospektif dengan pendekatan potong lintang, data diperoleh dengan cara mengumpulkan data rekam medik sebagai data sekunder. Data dianalisis dengan uji korelasi Gamma, diperoleh nilai p = 0,011 yang menyatakan ada hubungan yang bermakna antara tingkat pendidikan ayah dan keparahan infeksi virus dengue. Dan diperoleh juga nilai p = 0,002 yang menyatakan ada hubungan yang bermakna antara tingkat pendidikan ibu dan keparahan infeksi virus dengue. Kata kunci: tingkat pendidikan, infeksi virus dengue, anak